Peran MIise en Scene dalam Membangun Adegan Humor pada Film The Big 4 Karya Timo Tjahjanto - Felina, Khoirina Diva Nadelia; Hartanto, Denny Antyo; Wajihuddin (ROLLING, 2025)
Film combines narrative and cinematic elements, with mise-en-scene playing a crucial role in shaping visual storytelling. This research examines how mise-en-scene contributes to humor in The Big 4 by Timo Tjahjanto, analyzing aspects such as setting, costumes, makeup, lighting, and staging. Using Bordwell et al.'s mise-en-scene theory and Arthur Asa Berger's humor techniques—Language, Logic, Identity, and Action—this qualitative study divides the film into four scenes to identify dominant humor techniques. Examples include dialogue-based teasing (Language), absurd situations (Logic), identity contrasts, such as Alpha's transformation (Identity), and physical comedy, like Dina’s poisoned antics (Action). The findings highlight how visual elements and humor techniques work together to enhance storytelling and character development, demonstrating the integration of mise-en-scene and comedic elements in creating an engaging cinematic experience. This study emphasizes the role of mise-en-scene in supporting humor and enriching audience engagement.